Towards competence-based VET : dealing with the pitfalls - Biemans, Harm J. A. [Verfasser]; Wesselink, Renate [Verfasser]; Gulikers, Judith [Verfasser]; Schaafsma, Sanne [Verfasser]; Verstegen, Jos [Verfasser]; Mulder, Martin [Verfasser] (My University, 2009)
"This article builds on a previous 2004 Journal of Vocational Education and Training (JVET) contribution by Biemans et al., in which several possible pitfalls in designing and implementing competence-based education (CBE) were discussed. The present article reports on the results of an extensive research programme on competence development and CBE consisting of four empirical studies carried out in schools for secondary and higher vocational education in the life sciences in the Netherlands in the years 2004 to 2008. Based on the research findings, the article examines how the CBE pitfalls have been dealt with in Dutch VET. The conclusion can be drawn that the various pitfalls have received attention during the design and implementation of CBE, but not all problems have been solved yet. The article provides clues as to how the various pitfalls might be further addressed in the future to improve the quality of competence-based VET." (Autorenreferat, BIBB-Doku)
Keywords: L 6.2.1 Standards/Gütekriterien; L 1.3 Curriculumentwicklung; L 6.3.1 Diagnose- & Messinstrumente; T 3 Forschungsmethoden; I 2.2.1 Westeuropa; Berufsbildung; Kompetenzorientierung; Curriculumentwicklung; Kompetenzforschung; Niederlande